THERMODYNAMIC PROPERTIES OF AQUEOUS GE(IV) HYDROXIDE COMPLEXES FROM 25 TO 350°C: IMPLICATIONS FOR THE BEHAVIOR OF GERMANIUM AND THE GE/SI RATIO IN HYDROTHERMAL FLUIDS - Pokrovski G.S.; Schott J. (My University, 1998)
The stoichiometry and thermodynamic properties of Ge(IV) hydroxide complexes were generated from both solubility and potentiometric measurements. The solubility of the tetrahedral germanium oxide (GeO2(tetr)) was measured at temperatures from 25 to 350°C in acid to alkaline solutions at the saturated vapor pressure of the system (Psat). Potentiometric measurements were performed on GeO2-KOH aqueous solutions at temperatures from 21 to 200°C and Psat using a pH solid-contact glass electrode. Results indicate that Ge(OH)4°(aq) is the dominant Ge-bearing species at concentrations up to at least 0.05 m over a wide range of pH (0–8) and temperatures (20–350°C). GeO(OH)3− forms in significant amounts only in alkaline solutions (pH > 8–9). These results were combined with the available low-temperature solubility data on the hexagonal germanium oxide (GeO2(hex)) and the thermodynamic properties of GeO2(tetr) and GeO2(hex) to generate Ge(OH)4°(aq) and GeO(OH)3− thermodynamic parameters within the framework of the revised HKF equation of state (Helgeson et al., 1981; Tanger and Helgeson, 1988). Calculations carried out using these parameters indicate that the distribution of Ge hydroxide species as a function of pH and temperature is similar to that of silicon hydroxide complexes. However, the significant differences between Ge(OH)4°(aq) and Si(OH)4°(aq) enthalpies of formation and heat capacities can lead to large variations with temperature of Ge/Si ratios in solutions in equilibrium with Ge-bearing silicates. For example, calculations show that the Ge/Si ratio in a fluid in equilibrium with a Ge-bearing wollastonite (Ca(Si,Ge)O3) increases by an order of magnitude when temperature is raised from 25 to 500°C. This can be responsible for the high values of Ge/Si ratios measured in high temperature crustal fluids.